Polysaccharide as gelatin subtitute material in halal drug delivery system - Hayyun Durrotul Faridah; Tri Susanti (Journal of Halal Product and Research)
Drug delivery system describe the journey of a drug to get the target of action. The material used in drug delivery is very diverse and according to the therapymethod. So far, the use of gelatin in the pharmaceutical is very extensive, such as material in the drug delivery system. Gelatin can be produced from the extraction of animal collagen like from skin, bone and connective tissue. They are usually taken from the products of animal slaughterhouse products such as pigs and cattles. To produce a halal material, starting from the selection of basic materials until production of a material must be appropiate with Islamic rules. Like the selection of basic materials that getting from halal animals, the slaughter process is according to Islamic law and does not contain alcohol or other non-halal ingredients. However, today the use of pig skin as a gelatin base material is preferred because of its abundant availability and ease of processing. But actually pigs are animals that should not be consumed in Islam. The large number of pharmaceutical products derivating from pigs is a problem for a Muslim because it can be non-halal product. Therefore it is necessary to look for alternative gelatin as drug delivery system. One of the alternative material that can be used is a polysaccharide which is a natural polymer with very abundant availability in nature. For example carrageenan which is a polysaccharide extracted from the red seaweed, alginate extracted from brown seaweed, and xanthan gum which is the excretion of Xanthomonas campestris bacteria. The polysaccharide can be used as a halal drug delivery system and has the potential to be developed further so that it has better quality than gelatin.